Five benefits of online teaching in tertiary education - Huszti Ilona; Ilona Lekhner; Lechner Ilona; Густі Ілона; Лехнер Ілона (ДВНЗ «Донбаський державний педагогічний університет, 2024)
Abstract. The third decade of the 21st century started with horribly shocking news: the outbreak of the COVID-19 pandemic. The disease has altered and restructured all spheres of life and people around the globe had to conform to the new reality. In Ukraine, all-country quarantine was officially announced on 12 March, 2020, when the educational process transitioned to the online mode. It was not common and in the beginning, it caused enormous problems for both teachers and students. However, participants of the educational process familiarized themselves gradually with the online teaching/learning form. Its routine and methods were acquired. Thus, when on 24 February, 2022 the Russian-Ukrainian war started and martial law was announced in Ukraine, face-to-face teaching was quitted and once again, digital education was introduced. Fortunately, this caused fewer difficulties to instructors and students as they had already experienced a similar transition two years before. By this time, they had been well equipped with the knowledge on digital learning and the various methods to be applied in the current situation.
https://edu.forlan.org.ua/?page_id=112
Keywords: online teaching; tertiary education; COVID‑19 pandemic